Anti-Rubella IgM status in antenatal checkup visiting women - KC, KP; Malla, S; Ghimire, P; Khanal, SP; Dumre, SP (Journal of Nepal Health Research Council, 2010)
Background: Rubella is a viral infection. Congenital rubella syndrome is the most serious consequences of rubella which has been observed in pregnant women. This study has been done to reveal the association of rubella infection in women. Methods: The serum specimens were collected from women during their regular antenatal check up, in, was included in the study. Specimens were tested at NPHL every week following standard operating protocol of NPHL utilizing Human ELISA (German) kits and reagents. The results of the tests along with the clinical histories collected from the patient on a proforma file carried by the patients were analyzed following standard statistical tools. Results: During the three years study period, 320 serum samples were collected in 2006, 372 in 2007 and 400 in 2008, out of which 38 (11.87%), 72 (19.35%) and 49 (12.25%) of the women visiting NPHL during their antenatal checkup were found positive to anti-rubella IgM antibody respectively, indicating recent infection. Almost above 80% of the positive cases were from age group 20-30 years. Conclusions: The study showed the significant association of recent rubella infection in women which emphasizes requirement of adolescent or adult immunization with rubella vaccine at the earliest. Key words: anti-rubella IgM; congenital rubella syndrome; pregnant women; rubella. DOI: 10.3126/jnhrc.v7i2.3010 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 76-79